ROLE OF PUBLIC NOTARIES IN FAMILY LAW MATTERS IN SERBIAN LAW WITH SPECIAL EMPHASIS ON THE PRACTICE OF PUBLIC NOTARIES IN THE CITY OF NIŠ - Kocić, Jovana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
In this paper, the author gives an overview of the powers of public notaries in family law matters, prescribed by the Family Law and the Law on Public Notaries of the Republic of Serbia, to consider their adequacy and to identify possible shortcomings, to eliminate them in the future. This paper provides an analysis of the role of notaries public in drafting agreements on legal maintenance, concluding a marriage contract, contracts on the management and disposal of joint property of spouses, contracts on the division of joint property of spouses, contracts on management and disposal of property of legally incapable persons and the conduct of notaries public in the procedure of acknowledgment of paternity. In addition, the possibilities of extending the competencies of notaries public to the procedure for divorce by mutual consent, following the example of Slovenian law, were reviewed and the results of the research on the conduct of notaries public in the mentioned family law matter in the territory of the City of Niš for the period from September 1, 2014 to June 15, 2024, were presented, to obtain a more complete picture of the practical consequences of the envisaged legislative solutions.
Keywords: notaries; family law relations; practice of notaries public